Kingdom Tok: Legends and Prophecies in Honiara, Solomon Islands. Issue 3 (6th October 2015) - Maggio, Rodolfo
Abstract: K ingdom tok is an expression that is increasingly used in Honiara. It describes a set of ideas and practices related to what Solomon Islanders see as a recent 'season' in their history. Such a season is characterised by the reappropriation of particular meanings of their faith that they perceive as influenced by recent historical processes such as the colonial era, the introduction of Christianity, and the first few decades from independence. In terms of 'Kingdom', they envision the possibility to challenge political hierarchies, social stratification, and issues of governance, as well as to re‐define their identities in relation to a general state of empowerment. In Honiara, Pentecostal churches and groups with a strong identification with Judaism make use of K ingdom tok discourses. I claim that they experience the actualisation of K ingdom tok as concrete projects of social action and service provision, which they see as concrete alternatives to historical churches, the state, and the 'way of the waitman '.